DIAGNOSTIC PROBLEMS OF MUCOVISCIDOSIS AND WAYS OF SOLUTION IN RUSSIA - A. A. Baranov; N. I. Kapranov; N. Yu. Kashirskaya; L. S. Namazova-Baranova; V. D. Sherman; O. I. Simonova; A. Yu. Tomilova; K. V. Sevost'yanov; A. M. Pushkov; A. L. Vladykin; N. V. Shatokhin (Union of pediatricians of Russia, 2014)
Mucoviscidosis is a monogenic autosomal recessive caused by the CFTR gene mutations and characterized by pronounced genetic heterogeneity and clinical polymorphism, which emphasizes the need in comprehensive diagnosis and molecular-genetic verification of the final diagnosis. Quality and duration of a mucoviscidosis patient depend on early diagnosis and timely adequate therapy. The article presents mucoviscidosis diagnostic methods and protocols and capabilities of the modern molecular-genetic pathological diagnosis; a review of DNA diagnostic sets has been performed. As sets of some of the genes typical to the Russian population have not been registered in the Russian Federation, mutations in 20% of the patients cannot be specified. In order to solve this problem it is necessary to develop DNA diagnostic sets specific for the Russian Federation, ensure genetic diagnosis of the disease, including sequencing methods at the expense of the federal budget, increase the amount of information and improve quality of teaching this discipline to  students of medial universities and at postgraduate courses for appropriate specialists.